2022
DOI: 10.3389/fonc.2022.948293
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Exacerbation of varices following atezolizumab plus bevacizumab treatment of hepatocellular carcinoma: A case series and literature review

Abstract: Recently, a combined regimen of atezolizumab and bevacizumab (AB) treatment has been approved as a first-line treatment in patients with advanced hepatocellular carcinoma (HCC), contributing to prolonged survival. However, we often encounter cases where treatment must be discontinued due to the occurrence of adverse events. One of these events, which is often fatal, is gastrointestinal bleeding. To clarify the clinical effects of gastrointestinal bleeding after AB treatment, we evaluated patients with HCC who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“… 28 Although both mechanisms impair hemostatic function, the specific inhibition of circulating VEGF leads to reduced capillary bed density in the liver and increased pressure in the reticuloendothelial system, resulting in exacerbated varicose veins. 28 , 29 Consequently, it is postulated that variceal bleeding is more prone to occur in patients receiving atezolizumab plus bevacizumab than in those receiving lenvatinib.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Although both mechanisms impair hemostatic function, the specific inhibition of circulating VEGF leads to reduced capillary bed density in the liver and increased pressure in the reticuloendothelial system, resulting in exacerbated varicose veins. 28 , 29 Consequently, it is postulated that variceal bleeding is more prone to occur in patients receiving atezolizumab plus bevacizumab than in those receiving lenvatinib.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Another study reported five cases of UGI bleeding and two cases of exacerbated varices during Atezo + Beva treatment. 32 AEs of bleeding, such as ruptured varices, require temporary interruption of Atezo + Beva therapy, and it has been reported that, once gastrointestinal bleeding occurs, continuation of Atezo + Beva is difficult in some cases for the following reasons: rapid deterioration of hepatic reserve, rapid growth of HCC, and acquired resistance against Atezo + Beva. 33 , 34 Therefore, the present study focused on PH, which can be associated with varices, and efficacy and safety were compared between PH(−) and PH(+) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these possibilities are unlikely. In a meta-analysis of the risk of high-grade bleeding in patients with various cancers treated with BVZ, the risk was significantly higher in those who received 5 mg/kg per wk than those who received 2.5 mg/kg per wk[ 21 ]. However, none of the studies included in the meta-analysis examined patients with HCC.…”
Section: Discussionmentioning
confidence: 99%